The role of membrane transporters in ovarian cancer chemoresistance and prognosis - Cerovska, Ela; Elsnerova, Katerina; Vaclavikova, Radka; Soucek, Pavel (Expert opinion on drug metabolism & toxicology, 2017)
Ovarian cancer has the highest mortality rate of all cancers in women. There is currently no effective method for early diagnosis, limiting the precision of clinical expectations. Predictions of therapeutic efficacy are currently not available either. Specifically, the development of chemoresistance against conventional chemotherapy poses a fundamental complication. Some membrane transporters have been reported to influence chemoresistance, which is often associated with a poor prognosis. Areas covered: The aim of this article is to review the existing information about membrane transporters and their role in both ovarian cancer chemoresistance and its outcomes. We then highlight limitations of current methodologies and suggest alternatives providing avenues for future research. Expert opinion: Membrane transporters play an important role in development of chemoresistance and affect prognosis of ovarian cancer patients; however, due to variations in methodology and in patient populations, their specific roles have yet to be clarified. For further evaluation of the clinical utility of membrane transporters, it is essential to validate results and improve methods for marker assessment across laboratories. A promising area for future research is to identify the genetic variability in potential markers in peripheral blood. These markers would then stratify patients into defined groups for optimal intervention.
Keywords: membránové transportní proteiny; Drug Resistance, Neoplasm; Prognosis; prognosis; Ovarian Neoplasms; chemoresistance; lidé; Humans; Biomarkers, Tumor; nádorové biomarkery; Animals; Membrane Transport Proteins; membrane transporters; chemorezistence; protinádorové látky; Antineoplastic Agents; zvířata; Ovarian cancer; expression; ženské pohlaví; Female; prognóza; nádory vaječníků